2019
DOI: 10.1186/s12864-019-6035-0
|View full text |Cite
|
Sign up to set email alerts
|

MiR-190a potentially ameliorates postoperative cognitive dysfunction by regulating Tiam1

Abstract: Background: Postoperative cognitive dysfunction (POCD) affects a large number of post-surgery patients, especially for the elderly. However, the etiology of this neurocognitive disorder is largely unknown. Even if several studies have reported a small number of miRNAs as the essential modulatory factors in POCD, these findings are still rather limited. The aim of current study was to screen the POCD-related miRNAs in the hippocampus tissues and investigate the target genes of differentially expressed miRNAs an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 58 publications
1
15
0
Order By: Relevance
“…We found that miR-101b-3p abrogates cardiomyocyte hypertrophy and fibrosis (Pan et al, 2012;Lee et al, 2017) and miR-148b-3p, is downregulated in mitral regurgitation and heart failure (Chen et al, 2016; Figure 6A; Table 3). Literature also showed that miR-101b-3p suppresses Stc1 (Stanniocalcin 1) implicated in macrophage differentiation, preferentially M1 polarization, and contributes to the increase in expression of multiple inflammatory cytokines (Table 3; De Martino et al, 2009;Leung and Wong, 2021) Similarly, miR-190a-3p is shown to target and suppress Tiam1 that activates il17 promoter and increase inflammatory cytokines (Table 3; Kurdi et al, 2016. Liu et al, 2019.…”
Section: Np-6a4 Increased Mirnas That Inhibits Cardiac Fibrosis and Hypertrophy And Suppress Inflammatory Cytokinesmentioning
confidence: 99%
“…We found that miR-101b-3p abrogates cardiomyocyte hypertrophy and fibrosis (Pan et al, 2012;Lee et al, 2017) and miR-148b-3p, is downregulated in mitral regurgitation and heart failure (Chen et al, 2016; Figure 6A; Table 3). Literature also showed that miR-101b-3p suppresses Stc1 (Stanniocalcin 1) implicated in macrophage differentiation, preferentially M1 polarization, and contributes to the increase in expression of multiple inflammatory cytokines (Table 3; De Martino et al, 2009;Leung and Wong, 2021) Similarly, miR-190a-3p is shown to target and suppress Tiam1 that activates il17 promoter and increase inflammatory cytokines (Table 3; Kurdi et al, 2016. Liu et al, 2019.…”
Section: Np-6a4 Increased Mirnas That Inhibits Cardiac Fibrosis and Hypertrophy And Suppress Inflammatory Cytokinesmentioning
confidence: 99%
“…The miR-572 improves early postoperative cognitive dysfunction by down-regulating NCAM1 ( Yu et al, 2015 ). Meanwhile, the miR-190a improves postoperative cognitive dysfunction in mice by regulating the expression of Tiam1 ( Liu et al, 2019 ). The miRNA-146a protects mice from cognitive impairment caused by operation by inhibiting the neuroinflammation ( Chen L. et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, circRNAs may be related to the pathogenesis of PND ( Gao et al, 2020 ). Meanwhile, the up-regulated expression of miRNA-572 in hippocampal neurons contributes to the recovery of cognitive function in rats with PND ( Yu et al, 2015 ), and the miRNA-190a also plays a key role in the pathogenesis of PND ( Liu et al, 2019 ). However, the differential expression profiles and possible ceRNA networks caused by PND remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenesis of POCD is complex and lacks effective diagnosis and treatment. Therefore, several recent studies have focused on the epigenetic regulation of the pathogenesis of POCD to discover potential therapies (Li et al, 2015;Liu et al, 2019;Zhong and Xu, 2019). miRNAs and lncRNAs in the brain have been reported to contribute to POCD Su et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Genome analysis has been used to identify functional genes in POCD for several years (Li et al, 2015). For example, Liu et al (2019) found that many miRNAs were differentially expressed between POCD and control-aged mice (Chen et al, 2019;Su et al, 2019). Furthermore, long non-coding RNAs (lncRNAs) were found to be differentially expressed in mRNAs and might contribute to POCD .…”
Section: Introductionmentioning
confidence: 99%